Coping Behaviors of Young Men and Women with Different Health Levels - Оксана Е. Ельникова; Ирина В. Фаустова; Любовь Ю. Комлик (Российский психологический журнал, 2023)
Introduction. This paper addresses health issues of the modern young generation and introduces new experimental designs to examine the relationship between health and the most preferred coping strategies of young people, which can enable a broader study of the issue of health protection through the development of conscious and rational behaviors, including in stressful situations. The paper presents an analysis of the concept of health from the interdisciplinary perspective. The focus is on the necessity of considering a single sociopsychological aspect of health, including its somatic, social, and personal levels. Stress affects human health and stress resistance helps maintain mental and physical health.